Changes in the magnetic attraction by mineral water in the magnetic dental attachment. - Kusumadewi, An-Nissa; Damayanti, Lisda; Rukiah, Rukiah; Risdiana, Risdiana (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: The magnetic dental attachment is an integral component of the overdenture. Dental magnetic attachment will be in the oral cavity and is influenced by the oral environment. Previous study has shown that acid solutions contained in commonly consumed foods or drinks can corrode magnets and reduce magnetic attraction. Consuming mineral water in daily life is a common thing done by Indonesians. The objective of this research is to investigate the impact of mineral water on both the magnetic attraction and the occurrence of corrosion.Method: Mineral water which are sold commercially with different pH of 6.8 and 7.5, were used. Magnetic dental attachments were immersed in both types of mineral water for 7 and 14 days. The magnetic attraction was quantified by employing a materials testing machine and corrosion on the magnetic surface was seen using SEM. Result: After the immersion of magnetic dental attachments in mineral water with a pH level of 6.8 for 7 days and 14 days, magnetic attraction decreased by 5.36% and 21.77%, respectively. While after immersion at a pH level of 7.5 for 7 days and 14 days, magnetic attraction decreased by 9.39% and 22.89%, respectively. SEM examination showed that the surface of the magnetic dental attachment was corroded after being immersed in both types of mineral water and in both groups of immersion times.Conclusion: Immersing the magnetic dental attachment in the mineral water with different pH level decreased the magnetic attraction force as well as corroded the surface of magnetic dental attachment.